Comparison of the Effectiveness of Auditory Intellectually Repetition Method with Everyone Is Teacher Here in Chemistry Learning - Suri Pratimi, Renda; Urwatil Wutsqo Amry (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Studi Islam Sunan Doe, 2022)
Research on the Application of the Auditory Intellectually Repetition method with the Everyone is Teacher Here Method Measured by Motivation and Chemistry Learning Achievement on the Main Material Hydrocarbons is a quasi-experimental research type with a research design involving 3 classes, namely the first class is taught with the Auditory Intellectually Repetition method, Everyone Is Teacher Here method and the third class taught by a combination of them with different treatments. This research was conducted at MA Darussalam, Lombok, in the 2020/2021 academic year. This study aims to determine the differences in motivation and achievement in learning chemistry of students who are taught using the Auditory Intellectually Repetition learning model and Everyone Is Teacher Here method on the subject matter of hydrocarbons repetition with a combination of them on the subject matter of hydrocarbons, and knowing the differences in students' motivation and achievement in learning chemistry taught by those two methods. Based on the results of the study, it was found that there was a significant difference in the application of the Auditory Intellectually Repetition method with the Everyone Is Teacher Here method measured by motivation and achievement in learning chemistry on the subject matter of hydrocarbons.